2019
DOI: 10.1093/annonc/mdz177
|View full text |Cite
|
Sign up to set email alerts
|

FAIRLANE, a double-blind placebo-controlled randomized phase II trial of neoadjuvant ipatasertib plus paclitaxel for early triple-negative breast cancer

Abstract: Background: This hypothesis-generating trial evaluated neoadjuvant ipatasertib-paclitaxel for early triple-negative breast cancer (TNBC).Patients and methods: In this randomized phase II trial, patients with early TNBC (T ! 1.5 cm, N0-2) were randomized 1 : 1 to receive weekly paclitaxel 80 mg/m 2 with ipatasertib 400 mg or placebo (days 1-21 every 28 days) for 12 weeks before surgery. Co-primary end points were pathologic complete response (pCR) rate (ypT0/TisN0) in the intention-to-treat (ITT) and immunohist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
90
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 15 publications
2
90
0
Order By: Relevance
“…For therapeutic strategies involving AKT inhibitors, currently tested in TNBC, it might be promising to combine PIK3CA mutations with other alterations, such as AKT and PTEN, the combination of these 3 genes has been linked to response to AKT inhibitors in the Lotus and Manta studies (29,30), and a similar approach was investigated in the neoadjuvant Fairlane study (31). The rate of PIK3/AKT pathway alterations ranged from 23% to 43%, which was higher than the 8% in our study, which did not include PTEN loss.…”
Section: Discussionmentioning
confidence: 99%
“…For therapeutic strategies involving AKT inhibitors, currently tested in TNBC, it might be promising to combine PIK3CA mutations with other alterations, such as AKT and PTEN, the combination of these 3 genes has been linked to response to AKT inhibitors in the Lotus and Manta studies (29,30), and a similar approach was investigated in the neoadjuvant Fairlane study (31). The rate of PIK3/AKT pathway alterations ranged from 23% to 43%, which was higher than the 8% in our study, which did not include PTEN loss.…”
Section: Discussionmentioning
confidence: 99%
“…To develop an AKT-targeting heterobifunctional degrader, we designed compounds based on GDC-0068, the most advanced AKT inhibitor in clinical trials (Oliveira et al, 2019). The cocrystal structure of GDC-0068 bound to AKT1 (PDB ID: 4EKL) revealed that the isopropylamine is solvent-exposed, suggesting that the amine could serve as a suitable attachment site for linkers without adversely affecting affinity to AKT (Figure 1A).…”
Section: Design and Development Of The Pan-akt Degrader Iny-03-041mentioning
confidence: 99%
“…Current strategies to target AKT have focused on ATP-competitive, allosteric, and covalent inhibitors. Several ATP-competitive inhibitors, such as ipatasertib (GDC-0068) and capivasertib (AZD5363), are currently under clinical investigation in phase II and III studies (Oliveira et al, 2019;Turner et al, 2019). However, these inhibitors suffer from a lack of selectivity among the AGC kinase family, and this may limit their clinical efficacy or tolerability (Huck and Mochalkin, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recently an orally available PI3K alpha specific inhibitor termed Alpelisib has been approved for treatment of PIK3CA-mutated, hormone receptorpositive advanced breast cancer [3]. Akt inhibitors Capivasertib [4] and Ipatasertib [5] are in late stage clinical trials for breast cancers bearing PI3K or Akt mutations. However, studies to date indicate that despite encouraging initial responses, the majority of tumors display inherent resistance or develop acquired resistance to PI3K/Akt pathway inhibitors through diverse mechanisms [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…This targets SGK3 to endosomal membranes, where a large pool of PtdIns(3)P is generated by the Class III PI3K family member, known as hVps34 [17,19,20]. Activation of Class I PI3K can also contribute to the pool of PtdIns(3)P at the endosomal membrane through the sequential degradation of PtdIns (3,4,5)P3 via SHIP2 and INPP4A/4B inositol phosphatases [21,22]. Studies undertaken with selective class 1 and class 3 PI3K inhibitors indicate that both PI3K family members contribute to the activation of SGK3 by growth factors [22].…”
Section: Introductionmentioning
confidence: 99%